Lactic Acid Bacteria from Apis dorsata Hive Possessed Probiotic and Angiotensin-Converting Enzyme Inhibitor Activity - Meryandini, Anja; Karyawati, Amor Tresna; Nuraida, Lilis; Lestari, Yulin (UI Scholars Hub, 2020)
One source of bacteria that has not been widely explored is lactic acid bacteria originating from honeycomb (hive). Timor Island has a wealth of giant honey bees (Apis dorsata). Lactic acid bacteria from the Apis dorsata hive in Timor Island need to be investigated to obtain probiotic candidates with specific functional properties. Lactic acid bacteria were isolated from honeycomb by using de Mann, Rogosa, and Sharpe agar supplemented with 1% of CaCO3. Bacterial isolates that formed clear zones and were Gram-positive and catalase-negative were determined as lactic acid bacteria. The probiotic candidates are isolates that are resistant to bile salts and low pH; susceptible to antibiotics; are able to aggregate, autoaggregate, and coaggregate; and have antibacterial activities. Isolate MC7 was selected as a probiotic candidate and had inhibitory activity against angiotensin-converting enzyme (ACE) with IC50 263,098 ppm. Isolate MC7 showed weak inhibition against ɑ-glucosidase activity. Molecular identification based on 16S rRNA gene showed that MC7 isolate was closely related to Lactobacillus rhamnosus with 100% similarity. Therefore, isolate MC7 was recommended as a probiotic candidate with a functional property as an inhibitor of ACE.